2012
DOI: 10.1134/s0023158411060085
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and mechanism of ruthenium(III) catalyzed oxidation of chloromphenicol—An antibiotic drug by diperiodatocuprate(III) in aqueous alkaline medium

Abstract: The kinetics of ruthenium(III) catalyzed oxidation of chloramphenicol (CHP) by diperiodatocu prate(III) (DPC) in aqueous alkaline medium at a constant ionic strength of 0.1 mol l -1 was studied spectro photometrically. The reaction between DPC and CHP in alkaline medium exhibits 1 : 2 stoichiometry (CHP : DPC). The main oxidation products were identified by spot test, IR, NMR, and GC MS spectral studies. The reaction is first order with respect to ruthenium(III) and DPC concentrations. The order with respect t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 24 publications
0
5
0
1
Order By: Relevance
“…The uncatalyzed reaction of oxidation of chloramphenicol and ruthenium(III) catalyzed reaction has been studied. , Literature survey revealed that the role of Pd(II) and Os(VIII) catalysts on the oxidation of this drug has not been examined from the kinetic and mechanistic point of view. From preliminary investigations, we observed that Pd(II) and Os(VIII) in micro-amounts catalyzes the oxidation of CHP by DPC in alkaline medium.…”
Section: Introductionmentioning
confidence: 99%
“…The uncatalyzed reaction of oxidation of chloramphenicol and ruthenium(III) catalyzed reaction has been studied. , Literature survey revealed that the role of Pd(II) and Os(VIII) catalysts on the oxidation of this drug has not been examined from the kinetic and mechanistic point of view. From preliminary investigations, we observed that Pd(II) and Os(VIII) in micro-amounts catalyzes the oxidation of CHP by DPC in alkaline medium.…”
Section: Introductionmentioning
confidence: 99%
“…Antibiotics are generally liable to oxidation, resulting in their degradation and the termination of their action and/or their removal from the body. Therefore, one of the most favorable ways to achieve the decomposition of antibiotics is a treatment process resulting in their oxidation. Through such a process, oxidants may alter toxic compounds to less harmful ones, leading to their safe discharge to the environment. , An accurate literature survey illuminates little detailed kinetic studies for the oxidative degradation of antibiotics in an aqueous medium and/or such studies provide poor mechanistic information. The present investigation aims to provide a mechanistic picture for the biotransformation of antibiotics in the body as well as understanding how oxidation of certain functional groups in these organic molecules can affect antibiotic actions. In view of the forgoing aspects, the kinetics and mechanistic aspects of the oxidative degradation of two significant beta-lactam antibiotics, ampicillin and flucloxacillin, were investigated using hexacyanoferrate­(III) (HCF­(III)) as an efficient oxidant in an alkaline medium. …”
Section: Introductionmentioning
confidence: 99%
“…Thus, these materials are very dangerous pollutants for the ecological system and human health . Therefore, removal or degradation studies of antibiotics in aqueous media became part of significant environmental research. Conventional treatment technologies of pharmaceuticals pollution based on biological treatment are ineffective ways for removal of such harmful materials from water sources. , Nevertheless, chemical oxidation is a noteworthy manner for antibiotics degradation in aqueous media. Oxidation of pharmaceutical drugs plays a chief role in water treatment methods or in understanding drug metabolism in pharmacokinetic investigation. Chemical oxidation is considered as a more believable strategy for degradation of pharmaceutical drugs in wastewater and surface and ground water.…”
Section: Introductionmentioning
confidence: 99%